Tuktoyaktuk. Ultra high resolution orthomosaic - Vieira, Gonçalo; Pina, Pedro; Whalen, Dustin; Freitas, Pedro; Pinheiro, Daniel; Malenfant, François; Fraser, Paul; Robertson, Angus; Berry, Heather B. (Zenodo, 2020)
Aerial orthomosaic of the hamlet of Tuktoyaktuk - Poster A0. Survey conducted in July/August of 2018 and 2019 using a Sensefly ebee and a Sensefly ebee RTK Plus. Spatial resolution 10 cm.